Confidence in knowledge, childbirth fear, and preference for cesarean birth among Polish women: a cross-sectional study. - Surma, Patrycja; Micek, Agnieszka; Bednarek-Chałuda, Monika; Stoll, Kathrin; Nenko, Ilona (European Journal of Public Health, 2026)
In Poland, 48 in 100 babies are born by cesarean section, which is among the highest rate of cesarean birth (CB) in the Organization for Economic Cooperation and Development (OECD) countries. Several factors are linked to higher CB rates, including childbirth fear prior to pregnancy (CFPP), and physician versus midwifery led models of care. In order to decrease CB rates, it is crucial to understand modifiable factors that are associated with childbirth preferences. In this study, we tested how confidence in knowledge of pregnancy and birth was related to: (i) fear of childbirth, preference for: (ii) mode of birth and (iii) prenatal care provider type. We recruited 782 women aged 18–35 (mean 24.7, SD 3.19) who had never been pregnant but desired to have at least one child in the future. Women with moderate and high levels of confidence in knowledge had lower odds of high fear of childbirth compared to women with low levels of confidence (aOR = 0.57, 95% CI: 0.39–0.83 and aOR = 0.54, 95% CI: 0.33–0.88, respectively). Neither moderate nor high levels of confidence in knowledge were associated with a preference for CB (aOR = 1.10, 95% CI: 0.73–1.67 and aOR = 0.92, 95% CI: 0.55–1.55, respectively) compared to low levels. In addition, women with high levels of confidence in knowledge had significantly lower odds of preferring obstetricians (aOR = 0.49, 95% CI: 0.26–0.89), compared to midwives. Our study provides evidence that confidence in knowledge is related to fear of childbirth and prenatal care provider preferences.